2018
DOI: 10.1021/acs.nanolett.8b03208
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Thermoelectric Power from Graphene Quantum Dots

Abstract: The quantum confinement of charge carriers has been a promising approach to enhance the efficiency of thermoelectric devices, by lowering the dimension of materials and raising the boundary phonon scattering rate. The role of quantum confinement in thermoelectric efficiency has been investigated by using macroscopic device-scale measurements based on diffusive electron transport with the thermal de Broglie wavelength of the electrons. Here, we report a new class of thermoelectric operation originating from qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Recently, it has been reported a huge leap in the progress of PCE up to 23.3% from 3.8% in methylammonium lead iodide organic-inorganic hybrid perovskite compound (CH 3 NH 3 PbI 3 ) 3 , 4 . This unprecedentedly high value of PCE has been attributed to high bipolar charge carrier mobility ( 0.6 cm V s ) 5 , high absorption coefficient in visible light range, tunable bandgap, strong fluorescence quantum yield, balanced charge mobility (electron-hole), low rate of electron-hole pair recombination, high carrier lifetimes, and high diffusion lengths 6 10 . Also, the presence of an extraordinary optoelectronic properties in organic-inorganic hybrid lead-halide perovskite compounds have a wide application in photonics like light-emitting diodes, and lasers 8 , 11 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported a huge leap in the progress of PCE up to 23.3% from 3.8% in methylammonium lead iodide organic-inorganic hybrid perovskite compound (CH 3 NH 3 PbI 3 ) 3 , 4 . This unprecedentedly high value of PCE has been attributed to high bipolar charge carrier mobility ( 0.6 cm V s ) 5 , high absorption coefficient in visible light range, tunable bandgap, strong fluorescence quantum yield, balanced charge mobility (electron-hole), low rate of electron-hole pair recombination, high carrier lifetimes, and high diffusion lengths 6 10 . Also, the presence of an extraordinary optoelectronic properties in organic-inorganic hybrid lead-halide perovskite compounds have a wide application in photonics like light-emitting diodes, and lasers 8 , 11 14 .…”
Section: Introductionmentioning
confidence: 99%
“…For thermoelectric materials, phonon anharmonicity is an important topic because it helps to reduce the thermal conductivity and thus enhances the ZT value. There are many strategies to reduce the thermal conductivity, such as "Phonon-glass Electron-crystal" [257], "Phonon-liquid Electron-crystal" [258], and lowering the dimensions [259]. Several classes of thermoelectric materials are currently under investigation, including complex chalcogenides [260,261], skutterudites [262], half-Heusler alloys [263], and metal oxides [264], etc.…”
Section: Thermoelectrics and Low Thermal Conductivitymentioning
confidence: 99%
“…Tremendous efforts have been put into the improvement of thermoelectric performances using QD structures . Haskins et al .…”
Section: Properties Revealed By Computational Simulationsmentioning
confidence: 99%
“…[99] Tremendous efforts have been put into the improvement of thermoelectric performances using QD structures. [100][101][102] Haskins et al [103] explored the thermoelectric potential of SiÀ Ge QDSL using GKM and MD simulations. It was reported that the dot sizes and spacing play dominant roles in the lattice Table 1.…”
Section: Thermal Propertiesmentioning
confidence: 99%